LAW ENFORCEMENT AGAINST JUVENILE MOTORCYCLE THEFT OFFENSES: A STUDY AT THE NORTH SUMATRA REGIONAL POLICE - Andrie Ghaivany Purba; M. Citra Ramadhan; Wenggedes Frensh (SOSIOEDUKASI, 2026)
This thesis examines law enforcement against juvenile motorcycle theft, focusing on the North Sumatra Regional Police. It addresses three key issues: (1) the statutory framework governing theft; (2) the enforcement strategies applied to juvenile offenders; and (3) the institutional obstacles encountered in practice. Employing normative legal research with a descriptive-analytical design, the study relies on primary and secondary legal materials through a doctrinal approach. The findings indicate that theft is regulated under Article 362 of the Indonesian Criminal Code and Articles 476–477 of Law No. 1 of 2023 on the Criminal Code. The North Sumatra Regional Police implement both penal measures, through formal criminal proceedings, and non-penal approaches emphasizing prevention and diversion in handling juvenile offenders. Enforcement challenges stem from the absence of comprehensive implementing regulations and budgetary constraints imposed at the central level, which limit operational facilities and institutional capacity. The study underscores the need for regulatory clarity, adequate institutional support, and strengthened preventive mechanisms within the juvenile justice framework.